Occurrence and assemblage distribution of Giardia Duodenalis in symptomatic and asymptomatic patients in southeastern Iran (2019–2022) - Kareem Hatam-Nahavandi; Ehsan Ahmadpour; Mostafa Rezaeian; Hanieh Mohammad Rahimi; Ahmadreza Meamar; Milad Badri; Aida Vafae Eslahi; Hossein-Ali Rahdar; Solmaz Sepahi; Hamed Mirjalali; David Carmena (Gut Pathogens)
Abstract Background The ubiquitous protozoan parasite Giardia duodenalis is a major contributor to the global burden of diarrhoea, particularly in young children living in poor-resource regions. Although rarely mortal, giardiasis is associated with growth retardation and cognitive impairment in early childhood. Here we investigate the epidemiology of human giardiasis in Iranshahr (south-eastern Iran), a region where this information was previously lacking. Methods Stool samples were collected from 17,455 outpatients and inpatients attended at three major hospital settings during April 2020 and March 2022. Microscopy was used as a screening method for the presence of Giardia cysts, and the identification of G. duodenalis assemblages was carried out using PCR and Sanger sequencing. Results The overall prevalence of giardiasis was 1.87 (326/17,455; 95% CI: 1.7–2.1). Being female was positively associated with higher odds of giardiasis (p = 0.014). Individuals without diarrhoea were less likely to have giardiasis (p = 0.022). Individuals attending the Iran Hospital were more likely to harbour G. duodenalis infections compared to those attending at the Khatam Hospital and the Clinical Reference Laboratory (p = 0.001). Our sequence analyses revealed the presence of assemblages A (56.5%, 13/23), B (39.1%, 9/23), and A + B (4.4%, 1/23). No association was observed between the occurrence of a given assemblage and the occurrence of diarhroea. Conclusions Giardia infections were found at relatively low prevalence rates in both symptomatic and asymptomatic individuals seeking medical attention. Being female, having diarrhoea, and being sampled during 2020–21 were predictors of giardiasis. Although limited, our molecular data indicate that some Giardia infections may be zoonotic in nature. These data should be corroborated and expanded in future epidemiological studies targeting simultaneously human, animal, and environmental (water) samples to improve our understanding of the epidemiology of giardiasis in Iran.